NAPPN: Who We Are, Where We Are Going, and Why You Should Join Us!. Issue 1 (1st February 2019) - Carroll, April Agee; Clarke, Jennifer; Fahlgren, Noah; Gehan, Malia A.; Lawrence‐Dill, Carolyn J.; Lorence, Argelia
Abstract : Core Ideas: NAPPN is the North American Plant Phenotyping Network. We are a scientific community focused on high‐throughput plant phenomics. We promote cross‐disciplinary communication among the many fields that contribute to phenomics research. The area of high‐throughput plant phenomics focuses on developing and deploying hardware and software, including sensors, analysis techniques, and computational methods, with the requisite expertise to rapidly discover and measure a wide array of plant traits. From there, scientists in many disciplines are employed to generate the knowledge to develop plants and plant products that support humanity with reduced environmental impacts. To advance in an area that requires expertise from fields such as biology, computer science, engineering, mathematics, physics, and statistics, reaching out across disciplines is a must and training in new areas can help. Here we report on how the North American Phenotyping Network (NAPPN) was founded, describe its mission to bridge disciplinary and national boundaries, and outline future plans for its expansion. To get involved with NAPPN and join as a member at no cost, visit the organization's website at http://nappn.plant‐phenotyping.org/ .